The City as an Emotional Refuge for Abandoning Traditional Jewish Life: Anna Vygodskaia’s Experience as a Young Jewish Girl in St. Petersburg - Ginat, Avital (Mobile Culture Studies. The Journal, 2024)
In the second half of the nineteenth century, numerous young Jewish women hailing from Eastern Europe made the deliberate choice to depart their homes and familial environments in the shtetls of the Russian Pale of Settlement, opting instead for the big city. Driven by a desire to liberate themselves from the gender norms entrenched in their conventional domestic upbringing, these women aspired to establish autonomous lives that would not demand a complete detachment from their family or Jewish customs. Among the avenues facilitating social, economic, and personal autonomy was the enrollment in higher education institutions—an option that became available in the major cities of the Russian Empire during that era. This essay concentrates on the opportunities that urban life extended to women, as evidenced by the case study of Anna Pavolovna Vygodskaia (1868–1943), a Belarusian native, who courageously defied familial objections to enroll in women’s courses in St. Petersburg. Through her memoir, readers are granted insight into the emotional realm of a young woman raised in a traditional Jewish background, underscoring how women of that epoch capitalized on the prospects presented by Modernity to attain personal independence.